PATHO-BIOLOGICAL STUDIES OF PPR VIRUS IN EXPERIMENTALLY INFECTED GOATS WITH REFERENCE TO IMMUNOMODULATORY ACTIVITY OF NIGELLA. SATIVA SEEDS - K. Aqil; Muti-ur-Rehman Khan; A. Aslam; A. Javeed; R. Qayyum; S. Masood; A. W. Manzoor; F. Yasmeen; M. L. Sohail; S. Umar (Journal of Animal and Plant Sciences, 2018)
Peste des petits ruminants (PPR) is a transboundary viral disease of small ruminants that causes huge economic losses in developing world. The present project was aimed to report the gross and microscopic alterations and to evaluate the immunomodulatory and therapeutic response of N. Sativa in goats experimentally infected with peste des petits ruminants virus (PPR). For this purpose, twenty goats were divided into four groups (A, B, C & D). Goats of group A were fed N. Sativa seeds seven days prior to the inoculation of infection, while group C was given N. Sative seeds on the very day of infection inoculation. Group B and D were kept as positive and negative control, respectively. Clinical signs score, histopathological changes, haematology, liver function parameters, renal function parameters and serum biochemical parameters were recorded after every seven days, until 21st day post infection. Results revealed statistically significant changes between treatment and control groups. Haematological parameters (TLC, TEC, Hb, PCV) were significantly higher (P≤0.05) in N. Sativa treated group. Liver enzymes (ALP and AST) decreased significantly (P≤0.05) in group A throughout the course of the study. Creatinine was also significantly lower (P≤0.05) in N. Sativa fed goats as compared to control group on day 21. Serum protein, albumin, calcium, potassium and magnesium was significantly higher (P≤0.05) in group fed with N. Sativa seven days prior to infection. Likewise, clinical signs, histopathological scoring was significantly lower (P≤0.05) in treated group A. All these changes highlight the immunomodulatory action of dietary supplementation of N. Sativa and its role in suppressing the pathogenicity of PPR virus in goats.
Keywords: goats; histopathology; immunomodulation; Nigella Sativa; PPR